Dinamika Islamisasi di Nusantara dalam Perspektif Teori Asal Usul Saluran Penyeberangan dan Pola Perkembangan - Hasriani Hasriani; Eno Puspitasari; Erwin Erwin; Idrus L (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the dynamics of Islamization in the Indonesian Archipelago by integrating perspectives on origins, mechanisms of dissemination, and patterns of development within a conceptual-historical analytical framework. This study employs a qualitative, literature-based approach by examining various relevant primary and secondary sources in the historiography of Islam in the Indonesian Archipelago. The research findings indicate that the process of Islamization did not originate from a single region but was the result of multi-source interactions involving Arabs, Indians, Persians, and Chinese through global trade networks. The spread of Islam occurred through various channels such as trade, marriage, Sufism, education, art, and politics that interacted synergistically. The patterns of Islamic development across various regions of the Nusantara exhibit variations influenced by local geographical, social, and political conditions, yet share a common adaptive and accommodative character toward local cultures. These findings affirm that Islam in the Nusantara was formed through a dialogical process that produced a moderate and inclusive religious character, relevant within the context of contemporary multicultural societies.